Risco de progressão para demência em pacientes com comprometimento cognitivo leve e sintomas neuropsiquiátricos: revisão sistemática e metanálise da literatura - Raimundo Jorge Serra Duarte Vaz Mourão (2014)
Subjects with mild cognitive impairment (MCI) have an increased risk of developing dementia. It is a common occurrence of neuropsychiatric symptoms in MCI patients. Studies show divergent results to establish the relationship between progression to dementia in patients with mild cognitive impairment and neuropsychiatric symptoms. OBJECTIVES: To conduct a systematic review followed by meta-analysis of the literature to assess the risk of progression to dementia in patients with mild cognitive impairment and neuropsychiatric symptoms. METHODS: We performed a comprehensive survey of articles in electronic databases Medline, PsycINFO, and Scopus. We searched for longitudinal studies that consider conversion to dementia in patients with MCI and neuropsychiatric symptoms (depression, anxiety, apathy, psychosis and sleep and nighttime behavior disorders). The search was limited to articles published in the period from 01/01/1999 to 09/14/2014 and there was no language restriction. Data extraction was performed by two independent evaluators. Used a statistical method Mantel-Haenszel for dichotomous measures and the analysis of random models. RESULTS: A total of 16 studies were included in meta-analysis. Individuals with MCI and neuropsychiatric symptoms showed no significant risk of conversion to a dementia. There were 13 studies that evaluated the "depression" (OR = 1.41, 95% CI 0.91 - 2.18, p <0.05), 04 studies of "anxiety" (OR = 0.90, 95% Cl 0:52 to 1:55, p = 0.16), 06 studies "apathy" (OR = 0.89, 95% CI 0:50 to 1:57, P <0.05), 03 of studies "psychosis" (OR = 1.80, 95% Cl 0.75 - 4:33, p = 0:17). and 03 studies of "sleep and nighttime behavior disorders" (OR = 0.72, 95% Cl 0:39 to 1:32, p = 0:13) CONCLUSION: This is the first meta-analysis on the presence of neuropsychiatric symptoms, particularly depression, anxiety, apathy, psychosis and sleep and nighttime behavior disorders in elderly patients with CCL and the risk of progression of dementia. The main analysis showed no significant association between the presence of neuropsychiatric symptoms and the risk of progression of dementia in older people with MCI. However, subgroup analyzes showed that in communitybased studies, the presence of depressive symptoms in older adults with MCI increase the risk of progression to dementia.